Exploring the acceptability of the ‘smart cane’ to support mobility in older cancer survivors and older adults: A mixed methods study - Bluethmann, Shirley M.; VanDyke, Erika; Costigan, Heather; O'Shea, Charles; Van Scoy, Lauren Jodi (Journal of geriatric oncology, 2023)
Approximately 25% of older cancer survivors (i.e., ≥ 65 years, with cancer history) use ≥1 mobility device, surpassing usage by other older adults. Few tools exist for older “survivors” to regain function or follow lifestyle recommendations. Our goal was to explore opportunities to leverage technology-enabled mobility devices, such as the “smart cane,” to support mobility goals in these survivors. The research objective was to assess perceptions related to acceptability, usability and preferences of participants regarding technology-enabled mobility devices in everyday life. We used a convergent mixed-methods design, analyzing quantitative data followed by qualitative focus groups. A pre-survey derived from the Senior Technology Acceptance Model assessed the acceptability of technology-enabled devices among participants, who also participated in one of three focus groups delivered via Zoom. The Zoom sessions included facilitated 90-min discussions and video demonstration of the smart cane. Focus group sessions were recorded and transcribed verbatim and thematic content analysis was conducted. We recruited 12 older US survivors. Participants were 58% female, aged 68–86, and 16% non-White. From a pre-survey of participants, 83% said that they liked the idea of technology-enhanced mobility device and 100% said they thought they could be skillful at using a technology-enabled device if training was provided. Though participants were enthusiastic about the smart cane overall and felt the smart cane supported independence for older adults, the themes revealed concerns about safety, accessibility and technology support, as well as the concern for negative impact on self-image due to use of a mobility device. There was a strong preference for working with clinical professionals as the most trusted sources for referrals, if a smart cane was suggested. Older survivors in our sample found the smart cane very acceptable, and supportive of independence for older adults with cancer and other conditions. Participants also provided many insights that revealed additional research needed to support access, safety and usability for older adults, older survivors and caregivers, especially by partnering with clinical professionals.